1993
DOI: 10.1007/bf01088093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of blue green alga (Spirulina) on outcome of pregnancy in rats

Abstract: To study the supplementary effect of Spirulina, pregnant rats were fed 5 different kinds of diets (casein, Spirulina, wheat gluten, Spirulina + wheat gluten, Spirulina-without additional vitamins and minerals), each providing 22% protein during the period of pregnancy. The outcome of pregnancy was assessed from litter and dams' weight and litter size. Maternal weight gain was found to be maximum with Spirulina + wheat gluten and least with the wheat gluten diet. Rats receiving Spirulina containing diets produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The present study indicates that pigs fed a diet supplemented with PPEs for 11 days showed an increase in plasma Fe concentration and in Fe and Cu liver concetration evaluated as a measurement of mineral bioavailability. Chlorella vulgaris fed to pregnant mice also resulted in increase of serum Fe concentration (Janczyk, 2005), as it has also been reported for feeding rats with Spirulina (Kapoor and Mehta, 1993). Vyas et al (2009) demonstrated also in humans that the daily serving of a lucerne leaf concentrate powder was as effective as a daily tablet of Fe (60 mg as FeSO 4 ) in the treatment of anaemia in Indian adolescent girls, suggesting a better bioavailability of Fe and/or a synergistic effect of other components of leaf concentrate, even though it contains a lower Fe concentration (5 mg Fe) (Vyas et al, 2009).…”
Section: Discussionmentioning
confidence: 59%
“…The present study indicates that pigs fed a diet supplemented with PPEs for 11 days showed an increase in plasma Fe concentration and in Fe and Cu liver concetration evaluated as a measurement of mineral bioavailability. Chlorella vulgaris fed to pregnant mice also resulted in increase of serum Fe concentration (Janczyk, 2005), as it has also been reported for feeding rats with Spirulina (Kapoor and Mehta, 1993). Vyas et al (2009) demonstrated also in humans that the daily serving of a lucerne leaf concentrate powder was as effective as a daily tablet of Fe (60 mg as FeSO 4 ) in the treatment of anaemia in Indian adolescent girls, suggesting a better bioavailability of Fe and/or a synergistic effect of other components of leaf concentrate, even though it contains a lower Fe concentration (5 mg Fe) (Vyas et al, 2009).…”
Section: Discussionmentioning
confidence: 59%
“…Supplementation of Spirulina in the diet at the doses much higher than any anticipated human consumption did not cause any signs of embryotoxic effects. In another study with rats [102], the effects of Spirulina alone or in combinations with other supplements on pregnancy were investigated. Maximal maternal weight gain was associated with Spirulina /wheat gluten diet whereas wheat gluten diet resulted in least weight gain.…”
Section: Safety Profilementioning
confidence: 99%
“…One case of hepatotoxicity was possibly associated with Spirulina intake [101], although the patient also took three other medications. A case of rhabdomyolysis was recently reported as a result of Spirulina intake [102]. Finally, an association of Spirulina consumption and development of a mixed immunoblistering disorder with characteristic features of bullous pemphigoid and pemphigus foliaceus was reported in an 82-year-old healthy woman [103].…”
Section: Safety Profilementioning
confidence: 99%
“…Spirulina is fast emerging as a whole answer to the varied demands due to its impressive nutrient composition which can be used for therapeutic uses (Venkataraman, 1998). The United Nations World Food Conference declared spirulina as "the best for tomorrow" and it is gaining popularity in recent years as a food supplement (Kapoor and Mehta, 1993). The spirulina ability as a potent anti-viral (Gustafson et al, 1989;Hayashi et al, 1993;Patterson et al, 1993;Hayashi et al, 1996;Shih et al, 2003), anti-cancer (Suda et al, 1986;Pang et al, 1988;Schwartz et al, 1988;Lisheng et al, 1991;Mathew et al, 1995;Ismail et al, 2009), hypocholesterolemic and hypolipidemic (Devi and Venkataraman, 1983;Becker et al, 1986;Nakaya et al, 1988;Iwate et al, 1990;Nagaoka et al, 2005;Colla et al, 2008), antidiabetic (Parikh et al, 2001;Muthuraman et al, 2009) and health improvement (Annapurna et al, 1991) agent is gaining attention as a nutraceutical and a source of potential pharmaceutical.…”
Section: Introductionmentioning
confidence: 99%